Differential Root Exudation and Architecture for Improved Growth of Wheat Mediated by Phosphate Solubilizing Bacteria - Yahya, Mahreen; Islam, Ejaz ul; Rasul, Maria; Farooq, Iqra; Mahreen, Naima; Tawab, Abdul; Irfan, Muhammad; Rajput, Lubna; Amin, Imran; Yasmin, Sumera (Frontiers in Microbiology, 2021)
Phosphorous deficiency is a major challenge faced by global agriculture. Phosphate solubilizing bacteria (PSB) provide a sustainable approach to supply available phosphates to plants with improved crop productivity through synergistic interaction with plant roots. The present study demonstrates an insight into this synergistic P solubilizing mechanism of PSB isolated from rhizosphere soils of major wheat growing agro-ecological zones of Pakistan. Seven isolates were the efficient P solubilizers based on in vitro P solubilizing activity (233-365 μg mL-1) with a concomitant decrease in pH (up to 3.5) by the production of organic acids predominantly acetic acid (~182 μg mL-1) and gluconic acid (~117 μg mL-1). Amplification and phylogenetic analysis of gcd, pqqE and phy genes of Enterobacter sp. ZW32, Ochrobactrum sp. SSR and Pantoea sp. S1 showed the potential of these PSB to release orthophosphate from recalcitrant forms of phosphorus. Principal component analysis indicates the inoculation response of PSB consortia on the differential composition of root exudation (amino acids, sugars and organic acids) with subsequently modified root architecture of three wheat varieties grown hydroponically. Rhizoscanning showed a significant increase in root parameters i.e., root tips, diameter and surface area of PSB inoculated plants as compared to un-inoculated controls. Efficiency of PSB consortia was validated by significant increase in plant P and oxidative stress management under P deficient conditions. Reactive oxygen species (ROS) induced oxidative damages mainly indicated by elevated levels of Malondialdehyde (MDA) and H2O2 contents was were significantly reduced in inoculated plants by the production of antioxidant enzymes i.e., superoxide dismutase, catalase and peroxidase. Furthermore, the inoculation response of these PSB on respective wheat varieties grown in native soils under greenhouse conditions was positively correlated with improved plant growth and soil P contents. Additionally, grain yield (8%) and seed P (14%) was significantly increased in inoculated wheat plants with 20% reduced application of Diammonium Phosphate (DAP) fertilizer under net house conditions. Thus PSB capable of such synergistic strategies can confer P biofortification in wheat by modulating root morpho-physiology; root exudation and can alleviate oxidative stress under P deficit conditions.